ZSM-12 molecular sieve with hollow structure and preparation method thereof

By reacting with ZSM-12 molecular sieve treated with water vapor with materials such as inorganic alkali and aluminum under specific conditions, the problem of the inability to prepare hollow structure ZSM-12 molecular sieve in the prior art is solved, and the preparation of hollow structure is realized, which is suitable for industrial use. Production and expansion of application areas.

CN119320148AActive Publication Date: 2025-01-17CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310867533.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-15
Publication Date
2025-01-17
Estimated Expiration
2043-07-15

AI Technical Summary

Technical Problem

The prior art cannot effectively prepare ZSM-12 molecular sieve with hollow structures, which limits its expansion in catalysis and other applications.

Method used

By contacting ZSM-12 molecular sieve with water vapor for pretreatment, then reacting with materials such as inorganic alkali, aluminum source and silicon source under specific conditions, the material ratio is regulated to form a hollow structure, preventing the silicon source from entering the crystal skeleton, and stabilizing the crystal structure.

Benefits of technology

ZSM-12 molecular sieve with hollow structure was successfully prepared, which is suitable for large-scale industrial production and has expanded its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a ZSM-12 molecular sieve with a hollow structure and a preparation method thereof, the crystal form is a ZSM-12 molecular sieve structure, the ZSM-12 molecular sieve structure is characterized as a single crystal particle crystal with a hollow structure through a transmission electron microscope, the center part of the crystal is hollow, and the hollow structure is presented. The preparation method comprises the following steps: firstly, contacting a ZSM-12 molecular sieve with water vapor for treatment, then washing, separating and drying to obtain a material, uniformly mixing the material with inorganic alkali, an aluminum source, a silicon source and water for reaction, and finally washing, separating, drying and roasting to obtain the ZSM-12 molecular sieve. The invention provides a brand-new method for synthesizing the ZSM-12 molecular sieve with the hollow structure, the problem that the ZSM-12 molecular sieve with the hollow structure cannot be obtained by an existing method for synthesizing and preparing hollow zeolite in the field is solved, and the preparation method provided by the invention is simple in process route and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic synthesis, and relates to a zeolite material and a preparation method thereof, in particular to a ZSM-12 molecular sieve and a preparation method thereof. Background Art

[0002] Zeolite molecular sieve is a kind of microporous crystalline material with a skeleton structure, specific pore size and large specific surface area. It is widely used in the fields of catalysis and separation, especially in petroleum refining and processing, coal chemical industry, biomass industry and natural gas chemical industry.

[0003] ZSM-12 zeolite molecular sieve has a 12-membered ring pore structure. Its structure type is MTW type, with one-dimensional linear non-crossed 12-membered ring elliptical straight pores. It can show excellent catalytic performance in catalytic cracking, catalytic dewaxing, hydrocracking, reforming, aromatization, isomerization, alkylation and other reaction processes.

[0004] CN104437606A discloses a multi-layered ZSM-12 molecular sieve and a preparation method thereof. The preparation process comprises the following steps: mixing a silicon source, an aluminum source, an alkali source, water and a template agent in a certain proportion and stirring them uniformly; then adding the ZSM-12 molecular sieve and continuing to stir them uniformly to obtain a mixture; and placing the mixture in a reactor for crystallization to obtain the multi-layered ZSM-12 molecular sieve.

[0005] CN106966408A discloses a bifunctional template for guiding the synthesis of multi-level porous ZSM-12 type zeolite molecular sieves, its preparation and molecular sieves based thereon, which are characterized in that the bifunctional template is first prepared, and then the bifunctional template is used to prepare a mesoporous-microporous dual-pore multi-level porous ZSM-12 zeolite by a one-step hydrothermal crystallization method.

[0006] At present, hollow or hollow zeolite molecular sieve materials are a special type of functional materials. The research on related materials has become a hot topic in the field of chemistry and new materials. Hollow zeolite molecular sieves have unique physical and chemical properties such as multi-level structure and large specific surface area, showing broad application prospects in shape-selective adsorbents, catalysts, drug sustained-release agents and microreactors, and have received more and more attention.

[0007] CN102491366A discloses a method for preparing a hollow ZSM-5 nano zeolite. The method comprises treating the ZSM-5 nano zeolite with a mixture of a quaternary ammonium salt and sodium hydroxide in a molar ratio of 1:1, a mixture of a quaternary ammonium salt and potassium hydroxide in a molar ratio of 1:1, n-butylamine and a quaternary ammonium base at 80 to 200° C. for 10 to 200 hours to obtain a hollow ZSM-5 zeolite.

[0008] CN104591220A discloses a hollow beta zeolite and a preparation method thereof. First, water, an inorganic base, an aluminum source and the beta zeolite are sequentially mixed and stirred; then they are placed in a closed reactor and treated at a constant temperature for a certain period of time to obtain the hollow beta zeolite.

[0009] At present, there is no relatively mature technology for hollow structure ZSM-12 molecular sieves disclosed, and it is urgent to develop the preparation technology of hollow structure ZSM-12 molecular sieves and expand the application field of ZSM-12 molecular sieves. Summary of the invention

[0010] In view of the deficiencies in the prior art, the present invention aims to provide a hollow-structured ZSM-12 molecular sieve and a preparation method thereof, and provides a new method for synthesizing a ZSM-12 molecular sieve with a hollow structure, which overcomes the difficulty that the existing methods for synthesizing hollow zeolites in the art cannot obtain a ZSM-12 molecular sieve with a hollow structure. The preparation method provided by the present invention has a simple process route, does not add additional equipment or use expensive reagents, is easy to operate, and is particularly suitable for large-scale industrial production.

[0011] The present invention first provides a ZSM-12 molecular sieve with a hollow structure. The ZSM-12 molecular sieve has the following characteristics: the molecular sieve crystal form is characterized by an X-ray diffractometer as a ZSM-12 molecular sieve structure, and the transmission electron microscope is characterized as a crystal with a hollow structure of a single crystal particle, and the central part of the crystal is hollow, showing a hollow structure.

[0012] Further, as a specific embodiment, the particle diameter of the ZSM-12 molecular sieve crystal with a hollow structure is 50 to 800 nm, preferably 80 to 700 nm.

[0013] Further, as a specific embodiment, the shell thickness of the ZSM-12 molecular sieve crystal particles with a hollow structure is 20 to 350 nm, preferably 30 to 300 nm.

[0014] Further, as a specific implementation, the oxide silicon-aluminum ratio of the ZSM-12 molecular sieve with a hollow structure is 8-110, preferably 10-100.

[0015] Further, as a specific embodiment, the surface area of ​​the ZSM-12 molecular sieve having a hollow structure is 280 to 640 m 2 / g, preferably 300 to 600 m 2 / g.

[0016] Further, as a specific embodiment, the pore volume of the hollow ZSM-12 molecular sieve is 0.08 to 0.32 cm 3 / g, preferably 0.1 to 0.3 cm 3 / g.

[0017] Further, as a specific embodiment, the acid amount of the ZSM-12 molecular sieve with a hollow structure is 0.045 to 0.21 mmol / g, preferably 0.05 to 0.2 mmol / g.

[0018] The present invention also provides a method for preparing a ZSM-12 molecular sieve having a hollow structure, comprising the following steps:

[0019] (1) contacting the ZSM-12 molecular sieve with water vapor for treatment, and then washing, separating and drying;

[0020] (2) under mixing conditions, mixing the material obtained after drying in step (1), an inorganic base, an aluminum source, a silicon source, methyltriethylammonium chloride, and water to react, and washing, separating, and drying the reacted material;

[0021] (3) The solid phase material obtained after drying in step (2) is calcined to obtain a ZSM-12 molecular sieve.

[0022] The present invention also provides a method for preparing a H-ZSM-12 molecular sieve having a hollow structure, comprising the following steps:

[0023] S1, preparing a ZSM-12 molecular sieve precursor, comprising the following steps:

[0024] (1) contacting the ZSM-12 molecular sieve with water vapor for treatment, and then washing, separating and drying;

[0025] (2) under mixing conditions, mixing the material obtained after drying in step (1), an inorganic base, an aluminum source, a silicon source, methyltriethylammonium chloride, and water to react, and washing, separating, and drying the reacted material;

[0026] S2, subjecting the solid phase material obtained after drying in step (2) to ammonium exchange treatment;

[0027] S3. The material after the ammonium exchange treatment in step S2 is further washed, separated, dried and calcined to obtain H-ZSM-12 molecular sieve.

[0028] As a specific embodiment, in the above preparation method, the ZSM-12 molecular sieve in step (1) can be selected from commercially available ZSM-12 molecular sieves in the art, or synthesized using an existing method for synthesizing ZSM-12 molecular sieves. More specifically, the properties of the ZSM-12 molecular sieve zeolite are generally as follows: the particle diameter of the ZSM-12 molecular sieve crystal is 50 to 800 nm, the surface area is 300 to 740 m 2 / g, pore volume is 0.08~0.38cm 3 / g.

[0029] As a specific embodiment, in the above preparation method, the treatment temperature in step (1) is 350-730° C., preferably 400-700° C., and the treatment time is 2-8 hours, preferably 3-6 hours.

[0030] As a specific embodiment, in the above preparation method, the process of contacting the ZSM-12 molecular sieve with water vapor in step (1) is a gas-solid two-phase reaction, and the ZSM-12 molecular sieve is fully contacted with the water vapor gas for treatment. Specifically, the following operation method can be adopted, a bracket is placed in the reactor, the ZSM-12 molecular sieve is placed on the bracket, and a certain amount of water is added to the reactor at the bottom of the bracket; it is ensured that the ZSM-12 molecular sieve does not directly contact the liquid water, and the water vapor fills the entire reactor during the treatment, and the water vapor interacts with the ZSM-12 molecular sieve; further, in terms of weight ratio, the weight ratio of the ZSM-12 molecular sieve to water is 0.08 to 0.25, preferably 0.1 to 0.2.

[0031] As a specific embodiment, in the above preparation method, the washing, separation and drying in step (1) can be selected from various existing operation modes in the art. Preferably, in the present application, the washing is washing with deionized water until the filtrate is neutral, and the washing can be performed several times, and usually multiple washings are required. Separation is to separate the liquid-solid phase of the material stream obtained after washing, and any of the methods that can achieve liquid-solid phase separation, such as filtration and centrifugal separation, can be used. The drying is generally dried at 100-140°C for 5-15h.

[0032] As a specific embodiment, in the above preparation method, the inorganic base in step (2) is an alkali metal hydroxide, and the alkali metal can be at least one of lithium, sodium, and potassium, and can be specifically selected from one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide.

[0033] As a specific embodiment, in the above preparation method, the aluminum source in step (2) is an aluminum salt, preferably an aluminum-containing inorganic salt, and the acid ion of the aluminum salt can be one or more of sulfate, aluminate, nitrate, and chloride. Specifically, it can be selected from one or more of sodium aluminate, aluminum sulfate, aluminum chloride, and aluminum nitrate.

[0034] As a specific implementation, in the above preparation method, the silicon source in step (2) is a silicon-containing compound, which can be specifically selected from one or more of white carbon black, silica gel, and silica sol.

[0035] As a specific embodiment, in the above preparation method, the ratio of the inorganic base, aluminum source, silicon source, the material obtained after drying in step (1), MTEA, and water in step (2) is 0.8-2.5:1.2-2.7:2.5-6:8-25:0.8-2.2:100, preferably 1-2:1.5-2.5:2-4:10-20:1-2:100, based on the weight ratio of each material.

[0036] As a specific embodiment, in the above preparation method, the reaction in step (2) is carried out at a temperature of 70 to 150° C., preferably 80 to 120° C., and the reaction time can generally be controlled to be 13 to 22 hours, preferably 15 to 20 hours.

[0037] As a specific embodiment, in the above preparation method, the washing, separation and drying in step (2) can be selected from various existing operation modes in the art. Preferably, in the present application, the washing is washing with deionized water until the filtrate is neutral, and the washing can be performed several times. Usually, multiple washings are required, and specifically, the washing can be controlled within 1-10 times. Separation is to separate the liquid-solid phase of the material stream obtained after washing, and any of the methods that can achieve liquid-solid phase separation, such as filtration and centrifugal separation, can be used. The drying is generally dried at 80-150°C for 1-20h.

[0038] As a specific implementation, in the above preparation method, the ammonium exchange treatment in step S2 can adopt any of the existing ammonium exchange methods in the art; the ammonium exchange treatment is performed at least once, preferably 3 to 5 times.

[0039] As a specific embodiment, in the above preparation method, the ammonium exchange treatment in step S2 is to mix the solid phase material obtained after drying in step (2), ammonium salt and water for ion exchange treatment, wherein the mass ratio of the solid phase material obtained after drying in step (2), ammonium salt and water is 8-25:8-25:100, preferably 10-20:10-20:100.

[0040] As a specific implementation, in the above preparation method, the ammonium salt can be one or more of ammonium nitrate and ammonium chloride, preferably ammonium nitrate.

[0041] As a specific embodiment, in the above preparation method, the ion exchange treatment temperature is 70 to 100° C., preferably 80 to 90° C., and the ion exchange treatment time is 1 to 5 hours, preferably 2 to 4 hours.

[0042] As a specific embodiment, in the above preparation method, the washing, separation, drying and roasting in step S3 can be selected from various existing operation modes in the art. Preferably, in the present application scheme, the washing is to wash with deionized water until the filtrate is neutral, and the washing can be performed several times, usually multiple times, and can be specifically controlled to be 1-10 times. Separation is to separate the liquid-solid two-phase of the material stream obtained after washing, and any of the liquid-solid two-phase separation methods such as filtration and centrifugal separation can be used. The drying is generally dried at 80-150°C for 1-20h. The roasting is a high-temperature roasting treatment at 400-600°C for 1-10h, and the roasting is carried out in the presence of an oxygen-containing atmosphere (such as air or oxygen).

[0043] The technical effects and advantages of the hollow structure ZSM-12 molecular sieve and the preparation method thereof provided by the present invention are shown in the following aspects:

[0044] Based on the research and experiment on the preparation process of the existing disclosed molecular sieve with hollow structure, the existing disclosed method for preparing molecular sieve with hollow structure cannot be applied to the preparation of hollow structure ZSM-12 molecular sieve. This may be because different types of molecular sieves have different crystal structures, and the physical and chemical properties presented are also quite different. Just as the synthesis methods between different types of zeolites are not completely universal, the preparation method of molecular sieve with hollow structure cannot be directly transferred between zeolites of different properties, and different hollow structure molecular sieves cannot be obtained by directly replacing the raw material types. For example, conventional zeolite is treated with inorganic base, and a mesoporous structure can be produced in the zeolite crystal to obtain a mesoporous zeolite; however, CN104591220A can prepare hollow Beta zeolite under the joint action of inorganic base and aluminum source. Due to the special properties of ZSM-12 molecular sieve, the existing method cannot process ZSM-12 molecular sieve to obtain a hollow structure ZSM-12 molecular sieve.

[0045] In the preparation method of the present invention, the ZSM-12 molecular sieve is first pretreated with high-temperature water vapor. During the pretreatment process, the silicon and aluminum in the ZSM-12 molecular sieve crystals will be rearranged. After analysis, it is believed that the main reason may be that the aluminum element migrates to the outside of the crystal, and the aluminum element forms a gradient distribution inside and outside the crystal. The aluminum content outside the crystal increases, while the aluminum content inside decreases. This gradient distribution is conducive to the formation of a hollow structure.

[0046] In the preparation method of the present invention, the ZSM-12 molecular sieve treated with high temperature steam and other raw materials for synthesizing molecular sieves, such as inorganic base, aluminum source, silicon source, etc., continue to react, and regulate the proportion of each material within a certain range (it is quite different from the existing raw material proportion of preparing ZSM-12 molecular sieve, and it is not within the effective range of the current conventional hydrothermal synthesis reaction material proportion). During the reaction, the inorganic base, aluminum source, silicon source and the treated ZSM-12 molecular sieve react, and the aluminum element enters the outside of the ZSM-12 molecular sieve crystal, while the inside of the ZSM-12 molecular sieve crystal undergoes a dissolution reaction, thereby forming a hollow form. The secondary crystal reaction in this method is different from the hydrothermal synthesis reaction of the existing zeolite. During the reaction of this method, the silicon source will not enter the ZSM-12 molecular sieve crystal framework, and the template agent such as methyltriethylammonium chloride can stabilize the crystal structure and avoid the collapse of the crystal structure. It is analyzed that during the preparation process of this method, the silicon source only plays a role in stabilizing the system. In the absence of a silicon source, the zeolite cannot be effectively converted into a hollow structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a transmission electron microscope photograph of the sample obtained in Example 1.

[0048] Figure 2 This is a transmission electron microscope photograph of the sample obtained in Comparative Example 1.

[0049] Figure 3 This is the XRD spectrum of the sample obtained in Example 1.

[0050] Figure 4 The XRD spectrum of the sample obtained for Comparative Example 1. DETAILED DESCRIPTION

[0051] The technical solutions and effects of the present invention are further described below in conjunction with embodiments, but are not limited to the following embodiments.

[0052] In this paper, the pore structure of zeolite materials was characterized by N2 adsorption-desorption and tested by a physical adsorption instrument from Micromeritics, USA. Before the test, the samples were vacuum treated at 300℃ for more than 4h. The specific surface area, pore size and other parameters were calculated according to the BET and BJH formulas.

[0053] In this paper, the phase structure and crystallinity of zeolite materials were characterized by X-ray diffraction, and the test was carried out using a Japanese Rigaku D / max2500 X-ray diffractometer with Cu target, Kα radiation source, graphite monochromator, tube voltage 40 kV, tube current 80 mA, scanning range 5°~40°, step size 0.1°, and scanning speed 1° / min.

[0054] In this paper, the acid content of the zeolite material was measured by ammonia temperature-programmed desorption. The ammonia temperature-programmed desorption test was performed using an AutoChem II 2920 chemical adsorption instrument manufactured by Micromeritics, USA. First, under the protection of helium, the temperature was raised to 550°C at a rate of 10°C / min and maintained for 1 hour; then the temperature was lowered to room temperature (25°C) at a rate of 10°C / min, replaced with ammonia and adsorbed for 1 hour; then replaced with helium and heated to 600°C at a rate of 10°C / min.

[0055] In this paper, the crystal morphology of the zeolite material was characterized by transmission electron microscopy, using a high-resolution transmission electron microscope (TEM) from JEOL, Japan. The instrument model was JEM-2200FS field emission ultra-high resolution transmission electron microscope, with an acceleration voltage of 200KV and a point resolution of 0.19nm.

[0056] In this article, the chemical reagents used are all analytically pure chemical reagents and can be obtained by purchasing commercial products.

[0057] Example 1

[0058] Weigh ZSM-12 molecular sieve and water in a mass ratio of 15.5:100. Then place ZSM-12 molecular sieve and water above and below the support of the reactor respectively, without direct contact between the two, and then close the reactor for reaction, the reaction temperature is 550℃, and the reaction time is 8h. The reaction product is washed and filtered, and then dried to obtain the first material, the drying temperature is 120℃, and the drying time is 10h. Sodium hydroxide, aluminum nitrate, white carbon black, the first material obtained, methyltriethylammonium chloride, and deionized water are mixed in a mass ratio of 1.6:1.8:4:12:1.5:100, and continue to be loaded into a closed reactor for reaction, the reaction temperature is 110℃, and the reaction time is 23h. The reaction product is washed and filtered, and then dried to obtain the second material, the drying temperature is 120℃, and the drying time is 10h. Then, ammonium nitrate, the second material and water were mixed in a mass ratio of 16:15:100 for ammonium exchange treatment, the treatment temperature was 87°C, the treatment time was 3 hours, and the treatment was repeated 3 times. After the end, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours. Finally, it was calcined in air at 500°C for 10 hours, and the obtained sample was numbered C1. The crystal structure of the prepared sample belongs to ZSM-12 zeolite, and its crystal morphology is a hollow structure.

[0059] Example 2

[0060] Weigh ZSM-12 molecular sieve and water in a mass ratio of 10:100. Then place ZSM-12 molecular sieve and water above and below the support of the reactor respectively, without direct contact between the two, and then close the reactor for reaction, the reaction temperature is 400℃, and the reaction time is 4h. The reaction product is washed and filtered and then dried to obtain the first material, the drying temperature is 120℃, and the drying time is 6h. Sodium hydroxide, aluminum nitrate, white carbon black, the first material obtained, methyltriethylammonium chloride, and deionized water are mixed in a mass ratio of 1:1.5:2:10:1:100, and continue to be loaded into a closed reactor for reaction, the reaction temperature is 80℃, and the reaction time is 20h. The reaction product is washed and filtered and then dried to obtain the second material, the drying temperature is 120℃, and the drying time is 10h. Then, ammonium nitrate, the second material, and water are mixed in a mass ratio of 10:10:100 for ammonium exchange treatment, the treatment temperature is 90℃, the treatment time is 2h, and the treatment is circulated 3 times. At the end, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours. Finally, it was calcined in air at 500°C for 10 hours, and the obtained sample was numbered C2. The crystal structure of the prepared sample belongs to ZSM-12 zeolite, and its crystal morphology is a hollow structure.

[0061] Example 3

[0062] Weigh ZSM-12 molecular sieve and water in a mass ratio of 20:100. Then place ZSM-12 molecular sieve and water above and below the support of the reactor respectively, without direct contact between the two, and then close the reactor for reaction, the reaction temperature is 700℃, and the reaction time is 3h. The reaction product is washed and filtered, and then dried to obtain the first material, the drying temperature is 120℃, and the drying time is 10h. Sodium hydroxide, aluminum nitrate, white carbon black, the first material obtained, methyltriethylammonium chloride, and deionized water are mixed in a mass ratio of 2:2.5:4:20:2:100, and continue to be loaded into a closed reactor for reaction, the reaction temperature is 120℃, and the reaction time is 15h. The reaction product is washed and filtered, and then dried to obtain the second material, the drying temperature is 120℃, and the drying time is 10h. Then, ammonium nitrate, the second material and water were mixed in a mass ratio of 20:20:100 for ammonium exchange treatment, the treatment temperature was 80°C, the treatment time was 4h, and the treatment was repeated 3 times. After the end, the obtained solid sample was filtered several times, and then dried at 120°C for 10h. Finally, it was calcined in air at 500°C for 10h, and the obtained sample was numbered C3. The crystal structure of the prepared sample belongs to ZSM-12 zeolite, and its crystal morphology is a hollow structure.

[0063] Example 4

[0064] Weigh ZSM-12 molecular sieve and water in a mass ratio of 13.2:100. Then place ZSM-12 molecular sieve and water above and below the support of the reactor respectively, without direct contact between the two, and then close the reactor for reaction, the reaction temperature is 570℃, and the reaction time is 5h. The reaction product is washed and filtered, and then dried to obtain the first material, the drying temperature is 120℃, and the drying time is 10h. Sodium hydroxide, aluminum sulfate, silica gel, the first material obtained, methyltriethylammonium chloride, and deionized water are mixed in a mass ratio of 1.2:2.1:3.2:12.5:1.2:100, and continue to be loaded into a closed reactor for reaction, the reaction temperature is 110℃, and the reaction time is 22h. The reaction product is washed and filtered, and then dried to obtain the second material, the drying temperature is 120℃, and the drying time is 10h. Then, ammonium nitrate, the second material and water were mixed in a mass ratio of 17.2:16.3:100 for ammonium exchange treatment, the treatment temperature was 85°C, the treatment time was 3 hours, and the treatment was repeated 3 times. After the end, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours. Finally, it was calcined in air at 500°C for 10 hours, and the obtained sample was numbered C4. The crystal structure of the prepared sample belongs to ZSM-12 zeolite, and its crystal morphology is a hollow structure.

[0065] Example 5

[0066] Weigh ZSM-12 molecular sieve and water in a mass ratio of 17.4:100. Then place ZSM-12 molecular sieve and water above and below the support of the reactor respectively, without direct contact between the two, and then close the reactor for reaction, the reaction temperature is 670℃, and the reaction time is 7h. The reaction product is washed and filtered, and then dried to obtain the first material, the drying temperature is 120℃, and the drying time is 10h. Sodium hydroxide, aluminum chloride, silica sol, the first material obtained, methyltriethylammonium chloride, and deionized water are mixed in a mass ratio of 1.3:2.4:3.5:13.5:1.3:100, and continue to be loaded into a closed reactor for reaction, the reaction temperature is 90℃, and the reaction time is 25h. The reaction product is washed and filtered, and then dried to obtain the second material, the drying temperature is 120℃, and the drying time is 10h. Then, ammonium nitrate, the second material and water were mixed in a mass ratio of 16.5:11:100 for ammonium exchange treatment, the treatment temperature was 80°C, the treatment time was 3h, and the treatment was repeated 3 times. After the end, the obtained solid sample was filtered several times, and then dried at 120°C for 10h. Finally, it was calcined in air at 500°C for 10h, and the obtained sample was numbered C5. The prepared sample crystal structure belongs to ZSM-12 zeolite, and its crystal morphology is a hollow structure.

[0067] Comparative Example 1

[0068] The ZSM-12 molecular sieve was not pretreated.

[0069] Sodium hydroxide, aluminum nitrate, white carbon black, ZSM-12 molecular sieve, methyl triethyl ammonium chloride and deionized water were mixed in a mass ratio of 1.6:1.8:4:12:1.5:100, and then put into a closed reactor for reaction. The reaction temperature was 110°C and the reaction time was 23h. The reaction product was washed and filtered and then dried to obtain the second material. The drying temperature was 120°C and the drying time was 10h. Ammonium nitrate, the second material and water were then mixed in a mass ratio of 16:15:100 for ammonium exchange treatment. The treatment temperature was 87°C and the treatment time was 3h. The treatment was repeated 3 times. After the solid sample was filtered several times, it was dried at 120°C for 10h. Finally, it was calcined in air at 500°C for 10h, and the obtained sample was numbered C6. The crystal structure of the prepared sample belongs to ZSM-12 zeolite, but it is not a hollow structure.

[0070] Comparative Example 2

[0071] Weigh ZSM-12 molecular sieve and water in a mass ratio of 15.5:100. Then place ZSM-12 molecular sieve and water above and below the support of the reactor respectively, without direct contact between the two, and then close the reactor for reaction, the reaction temperature is 550℃, and the reaction time is 8h. The reaction product is washed and filtered, and then dried to obtain the first material, the drying temperature is 120℃, and the drying time is 10h. Sodium hydroxide, white carbon black, the first material obtained, methyltriethylammonium chloride, and deionized water are mixed in a mass ratio of 1.6:4:12:1.5:100, and continue to be loaded into a closed reactor for reaction, the reaction temperature is 110℃, and the reaction time is 23h. The reaction product is washed and filtered, and then dried to obtain the second material, the drying temperature is 120℃, and the drying time is 10h. Then, ammonium nitrate, the second material and water were mixed in a mass ratio of 16:15:100 for ammonium exchange treatment, the treatment temperature was 87°C, the treatment time was 3 hours, and the treatment was repeated 3 times. After the end, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours. Finally, it was calcined in air at 500°C for 10 hours, and the obtained sample was numbered C7. The prepared sample has a crystal structure belonging to ZSM-12 zeolite, but it is not a hollow structure.

[0072] Comparative Example 3

[0073] Weigh ZSM-12 molecular sieve and water in a mass ratio of 15.5:100. Then place ZSM-12 molecular sieve and water above and below the support of the reactor respectively, without direct contact between the two, and then close the reactor for reaction, the reaction temperature is 550℃, and the reaction time is 8h. The reaction product is washed and filtered, and then dried to obtain the first material, the drying temperature is 120℃, and the drying time is 10h. Sodium hydroxide, aluminum nitrate, the first material obtained, methyltriethylammonium chloride, and deionized water are mixed in a mass ratio of 1.6:1.8:12:1.5:10:, and continue to be loaded into a closed reactor for reaction, the reaction temperature is 110℃, and the reaction time is 23h. The reaction product is washed and filtered, and then dried to obtain the second material, the drying temperature is 120℃, and the drying time is 10h. Then, ammonium nitrate, the second material and water were mixed in a mass ratio of 16:15:100 for ammonium exchange treatment, the treatment temperature was 87°C, the treatment time was 3 hours, and the treatment was repeated 3 times. After the end, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours. Finally, it was calcined in air at 500°C for 10 hours, and the obtained sample was numbered C8. The crystal structure of the prepared sample belongs to ZSM-12 zeolite, and its crystal morphology is not a hollow structure.

[0074] Comparative Example 4

[0075] Weigh ZSM-12 molecular sieve and water in a mass ratio of 15.5:100. Then place ZSM-12 molecular sieve and water above and below the support of the reactor respectively, without direct contact between the two, and then close the reactor for reaction, the reaction temperature is 550℃, and the reaction time is 8h. The reaction product is washed and filtered and then dried to obtain the first material, the drying temperature is 120℃, and the drying time is 10h. Sodium hydroxide, aluminum nitrate, white carbon black, the first material obtained, and deionized water are mixed in a mass ratio of 1.6:1.8:4:12:100, and continue to be loaded into a closed reactor for reaction, the reaction temperature is 110℃, and the reaction time is 23h. The reaction product is washed and filtered and then dried to obtain the second material, the drying temperature is 120℃, and the drying time is 10h. Then, ammonium nitrate, the second material, and water are mixed in a mass ratio of 16:15:100 for ammonium exchange treatment, the treatment temperature is 87℃, the treatment time is 3h, and the treatment is circulated 3 times. At the end, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours. Finally, it was calcined in air at 500°C for 10 hours. The obtained sample was numbered C9. The prepared sample had an amorphous structure and was not crystalline.

[0076] Comparative Example 5

[0077] Weigh ZSM-12 molecular sieve and water in a mass ratio of 15.5:100. Then place ZSM-12 molecular sieve and water above and below the support of the reactor respectively, without direct contact between the two, and then close the reactor for reaction, the reaction temperature is 150°C, and the reaction time is 8h. The reaction product is washed and filtered, and then dried to obtain the first material, the drying temperature is 120°C, and the drying time is 10h. Sodium hydroxide, aluminum nitrate, white carbon black, the first material obtained, methyltriethylammonium chloride, and deionized water are mixed in a mass ratio of 1:0.5:0.2:10:0.5:100, and continue to be loaded into a closed reactor for reaction, the reaction temperature is 80°C, and the reaction time is 23h. The reaction product is washed and filtered, and then dried to obtain the second material, the drying temperature is 120°C, and the drying time is 10h. Then, ammonium nitrate, the second material and water were mixed in a mass ratio of 16:15:100 for ammonium exchange treatment, the treatment temperature was 87°C, the treatment time was 3 hours, and the treatment was repeated 3 times. After the end, the obtained solid sample was filtered several times, and then dried at 120°C for 10 hours. Finally, it was roasted in air at 500°C for 10 hours, and the obtained sample was numbered C10.

[0078] Table 1 Physicochemical properties of samples obtained in various embodiments and comparative examples

[0079]

[0080] Note: The present invention uses the sample obtained in Example 1 as a reference, and its crystallinity is set to 100%. The relative crystallinity of all other samples is obtained by comparing with the crystallinity of the reference. The original acid content of ZSM-12 zeolite is 0.152 mmol / g.

Claims

1. A ZSM-12 molecular sieve with a hollow structure, wherein the ZSM-12 molecular sieve has the following characteristics: the molecular sieve crystal form is characterized by an X-ray diffractometer as a ZSM-12 molecular sieve structure, and the transmission electron microscope is characterized as a single crystal particle with a hollow structure, the center part of the crystal is hollow, showing a hollow structure.

2. The ZSM-12 molecular sieve with a hollow structure according to claim 1, wherein The particle diameter of the ZSM-12 molecular sieve crystal with a hollow structure is 50 to 800 nm, preferably 80 to 700 nm; the shell thickness is 20 to 350 nm, preferably 30 to 300 nm.

3. The ZSM-12 molecular sieve with a hollow structure according to claim 1, wherein The oxide silicon-aluminum ratio of the hollow-structured ZSM-12 molecular sieve is 8 to 110, preferably 10 to 100; the acid content is 0.045 to 0.21 mmol / g, preferably 0.05 to 0.2 mmol / g.

4. The ZSM-12 molecular sieve with a hollow structure according to claim 1, wherein The surface area of ​​ZSM-12 molecular sieve with hollow structure is 280~640m 2 / g, preferably 300 to 600 m 2 / g; pore volume is 0.08~0.32cm 3 / g, preferably 0.1 to 0.3 cm 3 / g.

5. A method for preparing a ZSM-12 molecular sieve having a hollow structure, comprising the following steps: (1) treating the ZSM-12 molecular sieve by contacting it with water vapor, and then washing, separating and drying it; (2) under mixing conditions, the material obtained after drying in step (1), an inorganic base, an aluminum source, a silicon source, methyltriethylammonium chloride and water are mixed and reacted, and the reacted material is washed, separated and dried; (3) The solid phase material obtained after drying in step (2) is calcined to obtain a ZSM-12 molecular sieve.

6. A method for preparing a H-ZSM-12 molecular sieve having a hollow structure, comprising the following steps: S1, preparing a ZSM-12 molecular sieve precursor, comprising the following steps: (1) treating the ZSM-12 molecular sieve by contacting it with water vapor, and then washing, separating and drying it; (2) under mixing conditions, the material obtained after drying in step (1), an inorganic base, an aluminum source, a silicon source, methyltriethylammonium chloride and water are mixed and reacted, and the reacted material is washed, separated and dried; S2, subjecting the solid phase material obtained after drying in step (2) to ammonium exchange treatment; S3. The material after the ammonium exchange treatment in step S2 is further washed, separated, dried and calcined to obtain H-ZSM-12 molecular sieve.

7. The preparation method according to claim 5 or 6, wherein: The treatment temperature in step (1) is 350 to 730° C., preferably 400 to 700° C., and the treatment time is 2 to 8 hours, preferably 3 to 6 hours.

8. The preparation method according to claim 5 or 6, wherein: In the step (1), a gas-solid two-phase reaction occurs in the process of contacting the ZSM-12 molecular sieve with water vapor. The water vapor gas is fully contacted with the ZSM-12 molecular sieve for treatment. The following operation method is adopted: a bracket is placed in the reactor, the ZSM-12 molecular sieve is placed on the bracket, and water is added to the reactor below the bracket. It is ensured that the ZSM-12 molecular sieve does not come into direct contact with liquid water. During the treatment, the water vapor fills the entire reactor, and the water vapor interacts with the ZSM-12 molecular sieve. In terms of weight ratio, the weight ratio of the ZSM-12 molecular sieve to water is 0.08 to 0.25, preferably 0.1 to 0.

2.

9. The preparation method according to claim 5 or 6, wherein: The inorganic base in step (2) is an alkali metal hydroxide, the alkali metal is at least one of lithium, sodium and potassium, and the inorganic base is selected from one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide.

10. The preparation method according to claim 5 or 6, wherein: The aluminum source in step (2) is an aluminum salt, preferably an inorganic aluminum salt, and the acid ion of the aluminum salt is one or more of sulfate, aluminate, nitrate and chloride.

11. The preparation method according to claim 5 or 6, wherein: The aluminum source in step (2) is selected from one or more of sodium aluminate, aluminum sulfate, aluminum chloride and aluminum nitrate.

12. The preparation method according to claim 5 or 6, wherein: The silicon source in step (2) is a silicon-containing compound selected from one or more of white carbon black, silica gel, and silica sol.

13. The preparation method according to claim 5 or 6, wherein: Calculated by weight ratio of each material, the ratio of the inorganic base, aluminum source, silicon source, the material obtained after drying in step (1), MTEA, and water in step (2) is 0.8-2.5:1.2-2.7:2.5-6:8-25:0.8-2.2:100, preferably 1-2:1.5-2.5:2-4:10-20:1-2:

100.

14. The preparation method according to claim 5 or 6, wherein: The reaction in step (2) is carried out at a temperature of 70 to 150° C., preferably 80 to 120° C., and the reaction time is controlled to be 13 to 22 hours, preferably 15 to 20 hours.

15. The preparation method according to claim 6, wherein: The ammonium exchange treatment in step S2 is to mix the solid phase material obtained after drying in step (2), ammonium salt and water for ion exchange treatment, wherein the mass ratio of the solid phase material obtained after drying in step (2), ammonium salt and water is 8-25:8-25:100, preferably 10-20:10-20:

100.

16. The preparation method according to claim 6, wherein: The ammonium salt is one or more of ammonium nitrate and ammonium chloride, preferably ammonium nitrate.

17. The preparation method according to claim 6, wherein: The ion exchange treatment temperature is 70 to 100° C., preferably 80 to 90° C., and the ion exchange treatment time is 1 to 5 h, preferably 2 to 4 h.

18. The preparation method according to claim 6, wherein: The calcination in step S3 is carried out at a high temperature of 400 to 600° C. for 1 to 10 hours in an oxygen-containing atmosphere.

Citation Information

Patent Citations

  • Method for preparing hollow zeolite socony mobil-5 (ZSM-5) nanometer zeolite

    CN102491366A

  • Hollow beta zeolite and preparation method thereof

    CN104591220A

  • Difunctional template agent for oriented synthesis of hierarchical-pore ZSM-12 type zeolite molecular sieve, preparation method of such difunctional template agent and molecular sieve based on such difunctional template agent

    CN106966408A

  • ZSM-12 molecular sieve of multilayer structure and preparation method thereof

    CN104437606A

Cited By

  • High-crystallinity ZSM-12 molecular sieve as well as preparation method and application thereof

    CN120483184A

  • A high-crystallinity ZSM-12 molecular sieve and its preparation method and application

    CN120483184B